2019
DOI: 10.3390/molecules24193492
|View full text |Cite
|
Sign up to set email alerts
|

Steam Explosion Conditions Highly Influence the Biogas Yield of Rice Straw

Abstract: Straws are agricultural residues that can be used to produce biomethane by anaerobic digestion. The methane yield of rice straw is lower than other straws. Steam explosion was investigated as a pretreatment to increase methane production. Pretreatment conditions with varying reaction times (12–30 min) and maximum temperatures (162–240 °C) were applied. The pretreated material was characterized for its composition and thermal and morphological properties. When the steam explosion was performed with a moderate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…A reduction of the hydrolytic activity has been reported for a temperature of 180°C. This reduction fits with the formation of inhibitory furan components, which appear at HTP temperatures close to 180°C (severity factor around 4) (Steinbach et al, 2019). Indeed, after removing the liquid fraction, B 0 decreases but k H increases, which clearly points toward the solubilization of a large portion of the organic fraction, but also the presence of potentially inhibitory organics.…”
Section: Discussionsupporting
confidence: 62%
“…A reduction of the hydrolytic activity has been reported for a temperature of 180°C. This reduction fits with the formation of inhibitory furan components, which appear at HTP temperatures close to 180°C (severity factor around 4) (Steinbach et al, 2019). Indeed, after removing the liquid fraction, B 0 decreases but k H increases, which clearly points toward the solubilization of a large portion of the organic fraction, but also the presence of potentially inhibitory organics.…”
Section: Discussionsupporting
confidence: 62%
“…It can be concluded that increments in temperature, and consequently in pressure, act via hemicellulose and lignin removal mechanism to improve methane yield. Steinbach et al [78] reported that hemicellulose degradation by too severe steam explosion (with the severity parameter of S 0 > 4.3 min) caused drops in methane yield, whereas altering hemicellulose structure and increasing its porosity under moderate conditions (S 0 = 4.1 min) enhanced methane yield.…”
Section: Changes In Chemical Compositionmentioning
confidence: 99%
“…In a study by Steinbach et al, the steam explosion on rice straw was shown to increase biogas yield. The experiment was carried out with steam at 206 • C and at 18.5 bar for 30 min and resulted in increasing the porosity of biomass and yielded more water-soluble components [50]. Another study on producing biofuels from Miscanthus lutarioriparius (a type of indigenous African grass) indicated that the steam explosion increased biomass surface area, which in turn enhanced the final fuel yield [51].…”
Section: Fermentation Modelmentioning
confidence: 99%
“…In a similar manner, artificial intelligence can also be used to integrate waste heat from several untapped sources in a fossil fuel refinery. Marbe and Harvey [50] discussed the potential of integrating renewable energy systems along with biofuel gasification processes into a natural gas combined cycle for combined heat and power [60]. Salman et al [51] carried out a techno-economic assessment of using waste heat from a bio-fueled combined heat and power (CHP) plant to power three different gasifiers and generate biomethane [61].…”
Section: Equipmentmentioning
confidence: 99%